The Effect of Premiums, Investments, Claims, and Underwriting on RBC: Moderating Profitability in Insurance on the IDX 2020–2025 - Eva Anggra Yunita; Yanti Puji Astutie; Juli Riyanto Tri Wijaya; Bilqis Nur Syamsidah (Universitas Pancasakti Tegal, 2026)
This study examines the effects of premium income, investment returns, claim expenses, and underwriting results on risk-based capital (RBC), with profitability as a moderating variable, in insurance companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2025 period. This study employs a quantitative approach using secondary data obtained from the companies’ annual reports. The research population comprises 12 insurance companies listed on the IDX. A purposive sampling technique was applied, resulting in 72 observations from 12 companies. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA). The findings indicate that premium income has no significant effect on risk-based capital. Investment returns have a positive and significant effect on risk-based capital, whereas claim expenses have a negative and significant effect. Underwriting results also have a negative and significant effect on risk-based capital. Furthermore, profitability does not moderate the relationship between premium income, investment returns, claim expenses, or underwriting results and risk-based capital. These findings suggest that profitability does not strengthen or weaken the effects of the examined financial factors on the solvency level of insurance companies.